2015
DOI: 10.1140/epjc/s10052-015-3802-1
|View full text |Cite
|
Sign up to set email alerts
|

Effective Majorana mass and neutrinoless double beta decay

Abstract: The probability distribution for the effective Majorana mass as a function of the lightest neutrino mass in the standard three neutrino scheme is computed via a random sampling from the distributions of the involved mixing angles and squared mass differences. A flat distribution in the [0, 2π ] range for the Majorana phases is assumed, and the dependence of small values of the effective mass on the Majorana phases is highlighted. The study is then extended with the addition of the cosmological bound on the sum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…[55][56][57][58] This type of matrix is called the two zero flavor neutrino mass texture. If we require a nonvanishing effective neutrino mass M ee for the neutrino less double beta decay, 59,60 only four textures are compatible with observed data in the two zero flavor neutrino mass texture scheme.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…[55][56][57][58] This type of matrix is called the two zero flavor neutrino mass texture. If we require a nonvanishing effective neutrino mass M ee for the neutrino less double beta decay, 59,60 only four textures are compatible with observed data in the two zero flavor neutrino mass texture scheme.…”
mentioning
confidence: 58%
“…The upper limit of the magnitude of the effective neutrino mass is currently restricted to be |M ee | ≤ 0.20 − 2.5 eV; 85 however, in the future experiments, a desired sensitivity |M ee | ≃ a few 10 −2 eV will be reached. 93 Upcoming experiments for neutrinoless double beta decay and dark matter search to be useful to probe the possible linkage between M ee and M 1 .…”
Section: Cp Violating Phasesmentioning
confidence: 99%
“…In particular, the latter case has smaller |m ν e ν e | but it is consistent with a U(1) selection rule. It is also possible to random-generate the values of the Majorana phases [12,13,14]. In this case, one typically expects largish values of |m ν e ν e |.…”
Section: Expectation On Majorana Massesmentioning
confidence: 99%
“…It is suggested that | m * ee | = 1 meV may be regarded as a target value for the sensitivity of future experiments in case that NMO is verified by the forthcoming neutrino oscillation experiments [20]. This suggestion is justified by the fact that the probability for | m ee | to be lying below | m * ee | = 1 meV is tiny, given the latest neutrino oscillation data and the cosmological bound on neutrino masses [21,22,23,24,25]. For illustration, we have reproduced the three-dimensional graph of | m ee | in Fig.…”
mentioning
confidence: 99%
“…(8), requiring m 123 = 0, we get two familiar conditions α 12 = σ ± π and m 12 = m 3 tan 2 θ 13 , which are the same for | m ee | = 0 for the standard case of three-flavor mixing and have been extensively discussed in Refs. [19,20,21]. Therefore, the location of the contact point in the (ρ, m 1 )-plane depends on the exact value of σ.…”
mentioning
confidence: 99%